Potency of Ear Mushroom and Shrimp Head as Natural Flavoring on Variations of Drying Temperature - Suryani, Titik; Istiqomah, Nurul (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
Natural flavoring is a flavoring made from edible mushrooms as a flavor enhancer food of powder or liquid form. Ear mushrooms and shrimp heads contain high protein and glutamic acid and can be used as natural flavoring and give additional savory taste of food. The objective of this research was to analyze the total protein content and organoleptic quality of natural flavoring components of ear mushrooms and shrimp heads at various drying temperatures. This research method used a completely randomized design (CRD) and two treatment components. The first component was the ratio of ear mushroom and shrimp heads: (25g:75g), (50g:50g), and (75g:25g). The second component was different drying temperatures of 40°C and 50°C. The research results showed that the highest content of total protein and the best organoleptic quality of natural flavoring in the K1T2 treatment (25g ear mushrooms + 75g shrimp heads with 50°C drying temperature) was 35.67% ie dark brown color, savory taste, delicious aroma, very soft texture, and liked.